1993
DOI: 10.1177/000331979304401111
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Thrombus Mimicking Myxoma and Bilateral Pulmonary Artery Aneurysms in a Patient with Behçet's Disease—A Case Report

Abstract: A case of Behçet's disease, in which superior vena cava syndrome was the presenting feature is reported. Magnetic resonance imaging and echocardiography revealed a mass lesion in the right atrium. This patient developed bilateral pulmonary artery aneurysms postoperatively and represents one of the bizarre manifestations of Behçet's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…109 It was reported that the largest aneurysm was 7 cm, 109 and the mean diameter of aneurysms was 2.3±1.1 cm. 122 The present study, however, revealed much larger dimensions of PAAs with a mean diameter of 4.0 cm.…”
Section: Discussioncontrasting
confidence: 70%
“…109 It was reported that the largest aneurysm was 7 cm, 109 and the mean diameter of aneurysms was 2.3±1.1 cm. 122 The present study, however, revealed much larger dimensions of PAAs with a mean diameter of 4.0 cm.…”
Section: Discussioncontrasting
confidence: 70%
“…Ozkan et al (6) demonstrated that there is no difference in the prevalence of echocardiographic abnormalities between patients with BD and control subjects. Since the first description by Buge in 1977 (7) up to date, only about 50 cases have been reported (1,2,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The main differential diagnoses are primary heart tumour and infectious endocarditis. The differentiation from atrial myxoma is sometimes difficult based on the fact that the appearances of the myxoma may be atypical and the surface may be covered by thrombus (12,17). Imaging tests as CT chest, and MRN could be helpful in the assessment of thoracic manifestations of BD including thrombus of the systemic veins, heart and pulmonary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Only 10 cases have been reported to date in the English literature. [3][4][5][6][7][8][9][10][11] As well, pulmonary involvement with this disease is rare, with the usual clinical presentation of pulmonary involvement being recurrent massive hemoptysis. 10,12 Repetitive pulmonary embolism has been reported in only 3 cases.…”
Section: Discussionmentioning
confidence: 99%